(Nass = text) in the Classic Dictionaries of the Language (Linguist, 2025)
Linguistic article: (Nass = text) in the classic dictionaries of the language, monitoring its genres as well as its resources and its fields, process its syntax phonetically, linguistically and grammatically, analyze the tools used for its explanation and clarification then show its forms of development by examining the historical and cognitive path that these linguistic connotations may have taken in the old linguistic dictionaries. It is possible that this path - whatever the degree of sincerity it enjoys - can help the researcher to convey the meanings found in the depth of the linguistic article, and to evaluate the degree of attention paid by some ancient Arab linguists to this linguistic material (ie: the common and the unfamiliar between them). ; Then he refuted some unwarranted preconceptions, which include certain studies that did not go far in controlling and monitoring all uses of the term (Nass = text) in the lexical heritage.
Keywords: Text; meanings; classic dictionaries lexical heritage